Two New Methods for Solving the Path‐Based Stochastic User Equilibrium Problem. (15th June 2015) - Zhou, Bojian; Bliemer, Michiel C. J.; Bell, Michael G. H.; He, Jie
Abstract: In this article, we present two new methods for the path‐based logit stochastic user equilibrium problem, and investigate their convergence properties. First, a two‐level partial linearization method is proposed. Second, a dual method is developed. Both of these two methods use second‐order approximation of the objective function. Our novel methods are compared to Damberg's partial linearization method (Damberg, 1996), which is known to be one of the best performing methods. Numerical results on the different networks show that, if properly scaled, our new methods compare favorably to Damberg's method.